Implementation of Published Ifrs S1 and S2 Standards Globaly - Kusuma, Kezia Nabella; Gani, Lindawati (Dinasti Publisher, 2024)
The aim of this research is to evaluate company sustainability reporting based on IFRS S1 and S2 standards. Furthermore, this evaluation will ultimately produce recommendations for the company so that the company can maximize improvement efforts in producing sustainability reports according to standards for the coming financial year. The research will be conducted using qualitative methods. Researchers will evaluate the disclosure of Company Sustainability Reports using IFRS S1 and S2 guidelines. Evaluation is carried out by comparing the Sustainability Report of PT. Bank Mandiri in 2023 with sustainability reporting standards in accordance with IFRS S1 and IFRS S2. The results of this research evaluate the Company's Sustainability Report based on IFRS S1 and S2 standards. The company generally meets the requirements of IFRS S1, especially in governance disclosures, but is deficient in aspects of strategy and risk management. Disclosure of metrics and targets is still inadequate. The IFRS S2 evaluation shows that most of the requirements are met thanks to experience with TCFD and SE-OJK 16/2021, but strategic aspects related to climate change are still lacking. Despite progress, companies need to increase transparency and thoroughness in preparing sustainability reports according to more detailed standards.